AGRICULTURAL ENGINEERING IN UKRAINE: CHALLENGES AND DEVELOPMENT OPPORTUNITIES - SHARAPATIUK, MAKSYM (Herald of Khmelnytskyi National University. Technical sciences, 2024)
This article provides a comprehensive analysis of the current state and history of agricultural engineering in Ukraine since the country gained independence. It delves into the key stages of the industry’s development, including periods of growth, stabilization, and decline in production, as well as the primary factors that have influenced these processes over time. A particular focus is placed on the significant impact of the ongoing armed conflict with Russia, which has led to widespread destruction of production facilities, severe disruption of logistics networks, and a sharp reduction in investments within the sector. Despite these challenges, the article highlights how Ukrainian enterprises have demonstrated resilience by adapting to new conditions, adopting innovative approaches, and reorienting their strategies toward the domestic market. Furthermore, the article projects future trends and opportunities for the agricultural engineering sector in Ukraine. It emphasizes the crucial role that the restoration and modernization of metallurgical production will play in reviving the industry. The diversification of material supplies, the implementation of active state support measures, and the strengthening of international cooperation are also identified as key drivers for future growth. The article underscores the importance of adopting environmentally friendly and energy-efficient technologies, which will not only enhance the sustainability of the sector but also open new opportunities for expanding into global markets. In conclusion, despite the numerous and formidable challenges facing the agricultural engineering sector in Ukraine, the article asserts that there is significant potential for recovery and sustainable development. By leveraging effective state policies, embracing modern technologies, and fostering international collaboration, Ukraine can enhance the competitiveness of its agricultural machinery on the global stage. This, in turn, will contribute to bolstering the country’s economic security and ensuring a more stable and prosperous future for the agricultural engineering industry.